НЕЙТРОНОГРАФИЧЕСКОЕ ИССЛЕДОВАНИЕ СПЛАВА ВНЕДРЕНИЯ Ti1-xMoxN - Хидиров, И.; Парпиев, А.С.; Жаксимуратов, И.Ж.; Махмудов, Ш.А.; Гетманский, В.В. (SCIENCE and SOCIETY, 2021)
In this work, for the first time is carried neutron diffraction study of the crystal structure of the Ti1-xMoxN alloy in a bulk sample is carried out. It is shown that this alloy has a fcc structure described within the space group Fm3̄m. It was found that the crystal structure contains vacancies in the metal sublattice. Nitrogen atoms are located in octahedral interstices surrounded by titanium and molybdenum atoms.